Assessing the behavioural trajectories of terrorists: The role of psychological resilience. Issue 2 (4th May 2022) - Corner, Emily; Taylor, Helen; Clemmow, Caitlin
ABSTRACT: Within studies critically examining terrorist behaviour, the examination of mental health has largely focused on the relationship with the movement towards terrorist involvement. The impact of engagement in terrorism upon mental health has rarely been studied. However, recent research has shown that there is an association between terrorist engagement and the occurrence of mental health problems across the spectrum of terrorist involvement. This work therefore expands on previous research, and disaggregates three discrete stages of terrorist involvement; pre-engagement, engagement, and disengagement, to critically examine the role of psychological resilience on mental health. To determine whether psychological resilience protects against the negative psychological repercussions of terrorist involvement, we undertake cluster analyses. Results indicate that there is a subset of actors who demonstrate psychological resilience, and appear to maintain their mental health despite their experiences during involvement in terrorism.